Manajemen dan Rekayasa Lalu Lintas Kawasan CBD Kota Bekasi - Hermawan, Bobby Agung (Magister Pembangunan Wilayah dan Kota,Undip, 2016)
This study discusses the efforts to improve the performance of the traffic in the CBD area of Bekasi City with management and traffic engineering. The proposed strategy is the reduction of traffic flow conflict at the existing congestion spots on the main road corridors, which are Ahmad Yani street, KH. Noer Ali street, and Hasibuan street. Congestion occurs in the u-turn and intersection. The proposed treatment is closure U-turn, Kayuringin intersection and the prohibition of right turn and U-turn at the major roads of Mall MM intersection. As for the long term proposal is to build a flyover at the MM Mal Bekasi intersection, this proposal is recommended for long term treatment due to need high costs and substantial time for it. Further studies is needed as well.